The Application of W.E. Deming and J.M. Juran’s Quality Control and Leadership Theories at SMAN 1 Rejang Lebong - Sutrisno, Sutrisno; Trinanda, Ririn; Saan, Qhibah; Elda, Rusni; Sutarto, Sutarto (The Future of Education Journal, 2025)
The quality control and leadership theories of W.E. Deming and J.M. Juran discuss the control of service and product quality as well as leadership within an institution. Deming and Juran’s theories can be applied in educational institutions by carrying out control and evaluation processes to improve the quality of services provided to the community. Quality assurance in education enhances public trust and contributes to the branding of educational institutions. Leadership plays a significant role in educational settings, as effective leadership has implications for the quality of educational services. This article analyzes the application of Deming and Juran’s quality control and leadership theories at SMAN 1 Rejang Lebong.